Improve Student Effectiveness And Efficiency In Reading With Ability Using Scramble Technique At Sd Negeri 08 Pasar Surantih - Afridawanti Afridawanti (Fakultas Sastra Universitas Ekasakti, 2018)
To learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to